Arthroscopic Treatment of Intraosseous Ganglion Cyst of the Lunate Bone - Cerlier, Alexandre (Arthrosc Tech, 2015)
Intraosseous ganglion cysts are rare causes of wrist pain. Surgical treatment of this pathologic condition yields good results and a low recurrence rate. The main complications are joint stiffness and vascular disturbances of the lunate bone. Wrist arthroscopy is a surgical technique that reduces the intra-articular operative area and therefore minimizes postoperative stiffness. This article describes an arthroscopic technique used for lunate intraosseous cyst resection associated with an autologous bone graft in a series of cases to prevent joint stiffness while respecting the scapholunate ligament. This study was based on a series of 4 patients, all of whom had wrist pain because of intraosseous ganglion cysts. Arthrosynovial cyst resection, ganglion curettage, and bone grafting were performed arthroscopically. Pain had totally disappeared within 2 months after the operation in 100% of patients. The average hand grip strength was estimated at 100% compared with the opposite side, and articular ranges of motion were the same on both sides in 100% of cases. No complications were reported after surgery. On the basis of these results, arthroscopic treatment of intraosseous synovial ganglion cysts seems to be more efficient and helpful in overcoming the limitations of classic open surgery in terms of complications.